Clinical outcomes and frontal plane two-dimensional biomechanics during the 30-second single leg stance test in patients before and after hip abductor tendon reconstructive surgery. (July 2017) - Huxtable, Rose E.; Ackland, Timothy R.; Janes, Gregory C.; Ebert, Jay R.
Abstract: Background: Hip abductor tendon tears are a common cause of Greater Trochanteric Pain Syndrome. Conservative treatments are often ineffective and surgical reconstruction may be recommended. This study investigated the improvement in clinical outcomes and frontal plane two-dimensional biomechanics during a 30-second single leg stance test, in patients undergoing reconstruction. We hypothesized that clinical scores and pertinent biomechanical variables would significantly improve post-surgery, and these outcomes would be significantly correlated. Methods: Twenty-one patients with symptomatic tendon tears underwent reconstruction. Patients were evaluated pre-surgery, and at 6 and 12 months post-surgery, using patient-reported outcome measures, assessment of hip abductor strength and six-minute walk capacity. Frontal plane, two-dimensional, biomechanical variables including pelvis-on-femur angle, pelvic drop, trunk lean and lateral pelvic shift, were evaluated throughout a 30-second single leg stance test. ANOVA evaluated outcomes over time, while Pearson's correlations investigated associations between clinical scores, pain, functional and biomechanical outcome variables. Findings: While clinical and functional measures significantly improved ( P  < 0.05) over time, no significant group differences ( P  > 0.05) were observed in biomechanical variables from pre- to post-surgery. While five patients displayed a positive Trendelenburg sign pre-surgery, only one was positive post-surgery. Clinical outcomes and biomechanical variables during the single leg stance test were not correlated. Interpretation: Despite improvements in clinical and functional measures over time, biomechanical changes during a weight bearing single leg stance test were not significantly different following tendon repair. Follow up beyond 12 months may be required, whereby symptomatic relief may precede functional and biomechanical improvement. Highlights: Hip abductor tendon repair resulted in less pain, improved strength and walk capacity. Hip abductor tendon repair reduced the incidence of a positive Trendelenburg sign. Group mean improvement in weight bearing mechanics was not observed.